2017
DOI: 10.1016/j.amepre.2016.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Changing Perceptions of Harm of E-Cigarettes Among U.S. Adults, 2012–2015

Abstract: Introduction Although the impact of long-term use of electronic cigarettes (e-cigarettes) on health is still unknown, current scientific evidence indicates that e-cigarettes are less harmful than combustible cigarettes. The study examined whether perceived relative harm of e-cigarettes and perceived addictiveness have changed during 2012–2015 among U.S. adults. Methods Data were from Tobacco Products and Risk Perceptions surveys of probability samples representative of U.S. adults in 2012, 2014, and 2015. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
124
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 39 publications
6
124
2
1
Order By: Relevance
“…Another US national study found that in 2015, 45.5% of 18-24 year-olds and 36.8% of 25-34 year-olds believed that e-cigarettes are less harmful than cigarettes. 40 These estimates are higher than those we estimated in 2012-2013. We did not identify recent national data on snus use and perceptions.…”
contrasting
confidence: 55%
“…Another US national study found that in 2015, 45.5% of 18-24 year-olds and 36.8% of 25-34 year-olds believed that e-cigarettes are less harmful than cigarettes. 40 These estimates are higher than those we estimated in 2012-2013. We did not identify recent national data on snus use and perceptions.…”
contrasting
confidence: 55%
“…Specifically, we offer new empirical evidence to support the hypothesis that exposure to conflicting information could be related to observed trends in public knowledge and greater perceived harms associated with e-cigarette use over time. 14,15 This analysis further adds to the growing body of research establishing associations between exposure to conflicting information and cognitions or behavior in other health domains (e.g., nutrition, HPV vaccination). 7,10 Future research could explore other outcomes of exposure to conflicting e-cigarette information, which have been explored in other health domains, including public perceptions of uncertainty or confusion about e-cigarettes, perceived trust and credibility of science/health recommendations, and tobacco use behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…13 Conflicting information exposure may lead to confusion and lower perceived harms toward e-cigarette use, and these in turn may reduce support for regulating e-cigarettes. 13 Although recent articles have implicated conflicting information in shaping public knowledge and perceptions of e-cigarettes, 14,15 it is not known whether exposure to conflicting information about e-cigarettes does in fact influence beliefs about e-cigarette harms and benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The same visceral response has not been seen in regards to electronic cigarettes, which are frequently viewed as modern and trendy (McDonald & Ling, 2015; Wagoner et al, 2016). In contrast, anxiety might be more pertinent to e-cigarettes where consumers are frequently uncertain about the health effects and unknown risks of these novel products (Majeed et al, in press). …”
Section: Discussionmentioning
confidence: 99%